A Terminal Pleistocene/Early Holocene Environmental Record and Fluted Point from Twain Harte, California. (3rd July 2017) - Moratto, Michael J.; Davis, Owen K.; Davis-King, Shelly; Meyer, Jack; Rosenthal, Jeffrey; Sylwester, Laurie
ABSTRACT: Although more than 500 Clovis points have been found at no fewer than 60 locations in California, the age of these points remains problematic. Here we report stratified deposits more than 3 meters deep at a site in the central Sierra Nevada from which a Clovis point was recovered in 1969. Five radiocarbon ( 14 C) dates provide temporal control for terminal Pleistocene and early Holocene strata at the site, including the sediments in which the point reposed. We also report the analysis of pollen samples from these strata. Our research indicates that the Clovis point most likely dates to ∼11, 900–11, 400 cal yr BP. We interpret this, in the context of other fluted-point discoveries, to mean that Clovis lithic technology evidently persisted longer in the Far West than it did elsewhere in the U.S.